2007
DOI: 10.1167/iovs.06-1355
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Endocannabinoid System in Retinal Damage after High Intraocular Pressure–Induced Ischemia in Rats

Abstract: The original observation that retinal ischemia-reperfusion reduces endogenous AEA via enhanced expression of FAAH supports the deduction that this is implicated in retinal cell loss caused by high IOP in the RGC layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 61 publications
5
100
0
3
Order By: Relevance
“…The physiological importance of the endocannabinoid system in IOP regulation is further emphasized with the finding that 2-AG levels are significantly reduced in human glaucomatous ciliary muscle (Chen et al, 2005). In addition to these findings, endocannabinoids have been postulated to play a neuro-protective role in a high IOP-induced retina ischaemia model of glaucoma (Nucci et al, 2007). Anandamide/arachidonylethanolamide levels have been found to be increased in cornea, ciliary body, choroid and retina in patients with diabetic retinopathy and age-related macular degeneration (Matias et al, 2006), suggesting other ocular pathologies may also involve alterations in endocannabinoid signalling.…”
Section: Discussionmentioning
confidence: 98%
“…The physiological importance of the endocannabinoid system in IOP regulation is further emphasized with the finding that 2-AG levels are significantly reduced in human glaucomatous ciliary muscle (Chen et al, 2005). In addition to these findings, endocannabinoids have been postulated to play a neuro-protective role in a high IOP-induced retina ischaemia model of glaucoma (Nucci et al, 2007). Anandamide/arachidonylethanolamide levels have been found to be increased in cornea, ciliary body, choroid and retina in patients with diabetic retinopathy and age-related macular degeneration (Matias et al, 2006), suggesting other ocular pathologies may also involve alterations in endocannabinoid signalling.…”
Section: Discussionmentioning
confidence: 98%
“…Although, several studies have shown that topical administration of cannabinoids reduces IOP (Pate et al, 1995;Laine et al, 2001;Chien et al, 2003) by modulating both production and drainage of aqueous humor (Chien et al, 2003;Njie et al, 2006) a number of studies reported that cannabinoids exert neuroprotective effects in the eye against glutamate-induced excitotoxicity (Jarvinen et al, 2002;Crandall et al, 2007;Nucci et al, 2007bNucci et al, , 2008Duncan et al, 2011), with potential implications for the treatment of glaucoma. (Tomida et al, 2004;Yazulla, 2008).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Interestingly, some studies suggested that inhibition of glutamate release represents a key mechanism involved in neuroprotection mediated by the cannabinoid system (Braida et al, 2000;Sinor et al, 2000;Marsicano et al, 2003;Gobira et al, 2015;Lin et al, 2015). In 2007, our group using an animal model of acute glaucoma reported that inhibition of fatty acid amide hydrolase (FAAH) or administration of metanandamide, a stable analogue of anandamide, minimize RGC loss caused by ischemia/reperfusion and that MK801, a noncompetitive NMDA receptors antagonist, controls anandamide degradation through FAAH (Nucci et al, 2007b). Accordingly, it is likely that excitotoxic stimuli may affect the metabolism of endocannabinoids in the mammalian retina.…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Although the retina has no sensory innervations, substance P (SP)-and calcitonin gene-related peptide (CGRP)-containing amacrine and ganglion cells have been observed in the retina in various species including humans (49-51). Furthermore, several experimental studies have suggested that these neuropeptides are involved in various retinal diseases (52)(53)(54). Previously, an increase in SP and CGRP immunoreactivity was observed in the retina after electric stimulation of the trigeminal ganglion (55).…”
Section: Introductionmentioning
confidence: 99%